Hydrogen diffusion coefficient dependencies on hydrogen contents in PdAg alloys - Lewis, F.A.; Tong, X.Q.; Bucur, R.V.; Kandasamy, K. (My University, 1997)
Values of hydrogen diffusion coefficients, DH, calculated from measurements of hydrogen permeation through membranes, preferably require reference information concerning both surface and substrate bulk hydrogen contents n (H/M, atomic ratio). For satisfactory conditions of surface catalytic activity, appropriate values of n may also be able to be correlated with experimental parameters of temperature T and hydrogen chemical potential (as commonly represented either by hydrogen gas pressure p or electrode potential E) through p (E) - c (n) - T relationships. In cases of palladium and palladium alloys, estimations of DH dependencies on n at relatively low temperatures (e.g. 25°C) have been quite widely derived by breakthrough technique considerations of electrolytic experiments. Latterly, however, it has been evidenced that determinations of DH with initial membrane hydrogen contents of n > 0 can be substantially affected by strain gradients self induced by the diffusing hydrogen interstitials themselves. Assessments of such strain gradient influences on dependencies of DH on n have now been examined in the case of the Pd81Pt19Hn system. Substantial analogous influences on dependencies of DH on n in the case of the technologically important Pd77 Ag23Hn system have also been discussed in preliminary reports. The present paper is concerned with further consolidation of allied information for Pd77Ag23 alloys.
Keywords: Diffusion Coefficient; Hydrogen; Palladium; Silver